ANALISIS PENGARUH IMPLEMENTASI LAYANAN SAMSAT KELILING TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR RODA DUA DI KABUPATEN PAMEKASAN - Riskiyatur Rohemah; Nurul Kompyurini; Emi Rahmawati (Universitas Trunojoyo Madura, 2013)
The purpose of this research was to describe the implementation of Samsat Keliling services on taxpayers compliance of motorcycle both partially and simultaneously tested using variables of access taxes, facilities, complaint center, and the website. The primary data was gathered by survey questionnaire directly on the 100 taxpayers of motorcycle owner who used services samsat keliling. The sampling technique used was simple random sampling. The data analysis was done by using multiple linier regression and hypothesis T test and F test dan coefficient determination (R).The result showed, in partial test, the variable of access taxes and (R2) complaint center significantly influence taxpayers compliance of motorcycle owners. Although, the variable of facilities and the website were not significantly influence the taxpayers compliance. On the other hand, in simultaneous test, variable of access taxes, facilities, complaint center, and the website significantly influence taxpayers compliance of motorcycle owners.